Crop sampling protocols for micronutrient analysis - Stangoulis, James; Sison, Cristina (International Food Policy Research Institute, 2008)
It is well known that plant breeding is a numbers game, and that screening genotypes requires a substantial effort in both the field and the laboratory. Collecting a representative sample and minimizing soil and dust contamination from harvesting or postharvest processing equipment poses a considerable analytical challenge when breeding iron- and zinc-dense crops.